2023
DOI: 10.1007/s10995-022-03553-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Presence Anti-SARS-CoV-2 IgA in the Colostrum of Women Infected by COVID-19 During the Pregnancy in Neonatal Clinical Outcomes: A Cross-Sectional Study

Abstract: Objectives To describe the presence of anti-SARS-CoV-2 IgA and IgG in the blood and colostrum of women with COVID-19 infection during pregnancy and associate the presence of anti-SARS-CoV-2 IgA in colostrum with clinical symptoms of their newborns. Methods A cross-sectional study was developed with 165 participants with COVID-19 infection during pregnancy and their newborns. Data collected: characteristics COVID-19 infection in pregnant women, gestational age, and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…All studies detected specific immunoglobulins against SARS-CoV-2. Infection mainly induces the production of specific IgA antibodies [17,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]46,47,[83][84][85][86], while vaccination mostly elicits the IgG response [22,25,27,29,32,38,42,44,46,47]. From the included studies, it seems that maternal age and BMI do not influence antibody titers.…”
Section: Resultsmentioning
confidence: 98%
“…All studies detected specific immunoglobulins against SARS-CoV-2. Infection mainly induces the production of specific IgA antibodies [17,[30][31][32][33][34][35][36][37][38][39][40][41][42][43]46,47,[83][84][85][86], while vaccination mostly elicits the IgG response [22,25,27,29,32,38,42,44,46,47]. From the included studies, it seems that maternal age and BMI do not influence antibody titers.…”
Section: Resultsmentioning
confidence: 98%
“…They came from 21 countries, with 26 studies from China (31.7%). The earliest study start time is December 2019 ( 24 ), and the longest study span is 12 months ( 86 ). Thirteen studies reported both nucleic acid test results and antibody test results.…”
Section: Resultsmentioning
confidence: 99%
“…Such antibodies were still present at least ten months after infection. In Brazil, Dutra et al ( 86 ) conducted a cross-sectional study of 165 participants infected with SARS-CoV-2 during pregnancy and their newborns, collecting postpartum colostrum samples from mothers. The results showed that 117 (70.9%) women were positive for anti-SARS-CoV-2 IgA in colostrum and confirmed that the presence of anti-SARS-CoV-2 IgA in colostrum was independently associated with lower clinical signs in newborns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have provided evidence of the presence of anti-SARS-CoV-2 IgA antibodies in the colostrum of pregnant patients with COVID-19 infection [ 20 , 21 ]. This presence of anti-SARS-CoV-2 IgA has been associated with a reduced frequency of clinical symptoms in newborns [ 21 ]. Considering the significant increase in immunoglobulin expression in response to SARS-CoV-2 infection, it is worth exploring this topic further.…”
Section: Reviewmentioning
confidence: 99%